Coincidence of Sarcoidosis With Ankylosing Spondylitis in a 48-Year-Old Woman; A Therapeutic Challenge - Gholam Hossein Alishiri; Ehsan Rahmanian; Mahsa Ramezanpour (Baqiyatallah University of Medical Sciences, 2020)
Introduction: A case of pulmonary sarcoidosis is reported because of difficulties in diagnosis and treatment, including the co-existence of ankylosing spondylitis (AS) and severe corticosteroid dependence. Case Presentation: A 48-year-old nonsmoking woman referred to the hospital because of chronic nonproductive cough and dyspnea with a 10-year history of AS. Bilateral rhonchi was detected in lung auscultation. There was a significant limitation in lumbar activity and range of motion in flexion (positive Schober's test), extension, and lateral bending. In lumbosacral magnetic resonance imaging (MRI), irregularities in the sacroiliac joint and bilateral sacroiliitis were evident. The angiotensin-converting enzyme level was elevated. Biopsy in hilar lymphadenopathy by transbronchial lung biopsy was done, and the histopathological findings showed chronic non-necrotizing granulomatosis inflammation compatible with sarcoidosis. Anti-tumor necrosis factor drugs was effective on steroid-dependent coexisting of sarcoidosis and AS. The symptoms were absent in regular follow up. Conclusion: Pulmonary fibrosis due to sarcoidosis can be prevented by suitable treatment. Clinical trials are needed to confirm the impact of treatments with monoclonal antibodies against tumor necrosis factor (TNF), for curing sarcoidosis.